A comprehensive analysis of genetic diversity of EBV reveals potential high-risk subtypes associated with nasopharyngeal carcinoma in China. Issue 1 (4th June 2021) - Xue, Wen-Qiong; Wang, Tong-Min; Huang, Jing-Wen; Zhang, Jiang-Bo; He, Yong-Qiao; Wu, Zi-Yi; Liao, Ying; Yuan, Lei-Lei; Mu, Jianbing; Jia, Wei-Hua
Abstract: Epstein–Barr virus (EBV), a widespread oncovirus, is associated with multiple cancers including nasopharyngeal carcinoma (NPC), gastric cancer and diverse lymphoid malignancies. Recent studies reveal that specific EBV strains or subtypes are associated with NPC development in endemic regions. However, these NPC specific subtypes were only identified in a portion of infected individuals due possibly to the limited samples size studied or the complicated population structures of the virus. To identify additional high-risk EBV subtypes, we conducted a comprehensive genetic analysis of 22 critical viral proteins by using the largest dataset of 628 EBV genomes and 792 sequences of single target genes/proteins from GenBank. The phylogenetic, principal component and genetic structure analyses of these viral proteins were performed through worldwide populations. In addition to the general Asia-Western/Africa geographic segregation, population structure analysis showed a 'Chinese-unique' cluster (96.57% isolates from China) was highly enriched in the NPC patients, compared to the healthy individuals (89.6% vs. 44.5%, P < 0.001). The newly identified EBV subtypes, which contains four Chinese-specific NPC-associated amino acid substitutions (BALF2 V317M, BNRF1 G696R, V1222I and RPMS1 D51E), showed a robust positive association with the risk of NPC in China (Odds Ratio = 4.80, 20.00, 18.24 and 32.00 for 1, 2, 3 and 4 substitutions, respectively, P trend <0.001). Interestingly, the coincidence of positively selected sites with NPC-associated substitutions suggests that adaptive nonsynonymous mutation on critical proteins, such as BNRF1, may interact with host immune system and contribute to the carcinogenesis of NPC. Our findings provide a comprehensive overview of EBV genetic structure for worldwide populations and offer novel clues to EBV carcinogenesis from the aspect of evolution.